On-farm dietary supplementation of black seed (Nigella sativa) meal in goats: effects on physiological and metabolomic responses during transportation - Gurrapu, Priyanka; Batchu, Phaneendra; Shaik, Arshad; Terrill, Thomas H.; Kannan, Govind (Frontiers in Veterinary Science, 2026)
Black cumin or black seed (Nigella sativa) has many beneficial biological properties, and its processing for oil extraction produces a byproduct known as black seed meal (BSM), which is utilized as an animal feed supplement. An experiment was conducted on a commercial farm to determine the effects of BSM supplementation and long-duration transportation on stress and metabolomic responses and antioxidant and immune capacities in goats. Ninety-six uncastrated male Spanish goats (4–5 months old) were randomly divided into two treatment (TRT) groups. Forty-eight goats were fed a concentrate diet containing 15% BSM, and 48 goats were fed the same diet with no BSM (control, C) in separate corrals for 3 weeks with ad libitum water. On the day of the experiment, goats were loaded onto two identical trailers (5 × 2.3 m), with 40 goats/trailer (20 goats/TRT), and were transported for 16 h to simulate a commercial situation. Blood samples were collected at 0 h (15 min after loading), 2 h, 4 h, 10 h, and 16 h of transportation (Time; n = 8 goats/Time/TRT) by jugular venipuncture. The dietary BSM supplementation in goats did not affect stress responses, except for tyramine (p < 0.05), but Time significantly affected (p < 0.05) plasma epinephrine, metanephrine, and normetanephrine. The BSM supplement did not significantly affect the antioxidant and immune status variables. At the metabolome level, 15 amino acids, 4 acylcarnitines, 24 phosphatidylcholines and sphingomyelins, and 13 other metabolites were significantly affected (p < 0.05) by TRT. Acylcarnitine (C2), hexadecenoylcarnitine (C16:1), hydroxybutyrylcarnitine (C4OH), β-hydroxybutyric acid, and iso-butyric acid concentrations were higher (p < 0.05) in the BSM goats, indicating energy supply was mainly through lipid metabolism. The BSM group had lower (p < 0.05) concentrations of glucose, 11 of the amino acids, and TCA cycle metabolites compared to the C group. Supplementation of BSM in the meat goat diet prior to extended road transportation may help them use fat as an energy source instead of breaking down protein. However, at a 15% level, there were no significant effects on antioxidant and immune status indicators determined.